1967
DOI: 10.1149/1.2426605
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Thermal Etching of Germanium and Silicon Surfaces

Abstract: The surface structures formed on {111}, {110}, and {112} surfaces of silicon and germanium heated in the temperature ranges 900°–1380°C for silicon and 650°–937 °C (mp) for germanium have been detailed. The changes in topography were found to be markedly dependent on the degree of undersaturation maintained during heating, as well as on the temperature range. The {111} surface of germanium was particularly sensitive to surroundings of the crystal. The proximity and shape of the surroundings influenced the free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

1969
1969
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…The decreases in A and $ with increasing surface roughness as indicated in this experiment is in agreement with the trend suggested by these studies. Roughened surfaces of silicon single crystal due to heating are also reported by several workers [8].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The decreases in A and $ with increasing surface roughness as indicated in this experiment is in agreement with the trend suggested by these studies. Roughened surfaces of silicon single crystal due to heating are also reported by several workers [8].…”
Section: Discussionsupporting
confidence: 65%
“…These impurities cannot be detected by Auger electron spectroscopy. However, the micrographs and electron micrographs of roughened surfaces taken by several workers [8] differ from each other; even complete smoothness was observed at every heating temperature [ 111. This suggests that the surface roughness is quite sensitive to the conditions of surface treatment ,and heating.…”
Section: Discussionmentioning
confidence: 99%
“…Such defects mostly emerge during thermal treatments required for surface preparation before epitaxial growth. In particular, thermal etch pits have been reported during the annealing of Ge wafers under vacuum [8] [9]. Density and morphology of these defects depend on the experimental conditions such as temperature, duration of annealing, number of thermal cycles, and wafer orientation.…”
Section: Introductionmentioning
confidence: 99%
“…There are several methods to etch the native oxide, such as, chemical etching with hydrofluoric (HF) acid, thermal etching at high temperatures that is commonly used in the study of surface structures on silicon, and by ion beam sputtering process, etc. Russel et al reported the vacuum thermal etching of silicon and germanium surfaces in the temperature regime of 900–1300 °C . Hopper et al.…”
Section: Introductionmentioning
confidence: 99%
“…Russel et al reported the vacuum thermal etching of silicon and germanium surfaces in the temperature regime of 900−1300 °C. 18 Hopper et al reported the removal of the oxide layer by flashing at ∼1200 °C and ion bombardment to obtain an optically flat silicon substrate under ultrahigh vacuum conditions. 17 Futagami et al reported the thermal etching of Si(100) at 1200 °C in argon atmosphere.…”
Section: ■ Introductionmentioning
confidence: 99%